Dosimetric considerations and early clinical experience of accelerated partial breast irradiation using multi-lumen applicators in the setting of breast augmentation - Akhtari, Mani; Pino, Ramiro; Scarboro, Sarah B.; Bass, Barbara L.; Miltenburg, Darlene M.; Butler, E. Brian; Teh, Bin S. (Journal of Contemporary Brachytherapy, 2015)
Purpose: Accelerated partial breast irradiation (APBI) is an accepted treatment option in breast-conserving therapy for early stage breast cancer. However, data regarding outcomes of patients treated with multi-lumen catheter systems who have existing breast implants is limited. The purpose of this study was to report treatment parameters, outcomes, and possible dosimetric correlation with cosmetic outcome for this population of patients at our institution. Material and methods : We report the treatment and outcome of seven consecutive patients with existing breast implants and early stage breast cancer who were treated between 2009 and 2013 using APBI following lumpectomy. All patients were treated twice per day for five days to a total dose of 34 Gy using a high-dose-rate 192Ir source. Cosmetic outcomes were evaluated using the Harvard breast cosmesis scale, and late toxicities were reported using the Radiation Therapy Oncology Group (RTOG) late radiation morbidity schema. Results: After a mean follow-up of 32 months, all patients have remained cancer free. Six out of seven patients had an excellent or good cosmetic outcome. There were no grade 3 or 4 late toxicities. The average total breast implant volume was 279.3 cc, received an average mean dose of 12.1 Gy, and a maximum dose of 234.1 Gy. The average percentage of breast implant volume receiving 50%, 75%, 100%, 150%, and 200% of the prescribed dose was 15.6%, 7.03%, 4.6%, 1.58%, and 0.46%, respectively. Absolute volume of breast implants receiving more than 50% of prescribed dose correlated with worse cosmetic outcomes. Conclusions : Accelerated partial breast irradiation using a multi-lumen applicator in patients with existing breast implants can safely be performed with promising early clinical results. The presence of the implant did not compromise the ability to achieve dosimetric criteria; however, dose to the implant and the irradiated implant volume may be related with worse cosmetic outcomes.